We can work it out: Popular and academic writing on The Beatles. (25th June 2015) - Collins, Marcus
Abstract : This article surveys the evolution of popular and academic research on The Beatles from the 1960s to the present. The section on popular writing identifies and critiques four strands of popular writing on The Beatles: hagiographical and sensationalist biographies, rock criticism and chronicling. The section on academic writing argues that traditionalist academics initially opposed the very idea of scholarship on The Beatles and that contemporary British historians still question the band's significance as part of their wider revisionist critique of the 1960s as a major turning-point in modern British history. The article concludes by suggesting how academics might profitably pursue a less biographical approach and a more rigorous form of source analysis than that generally found in popular works.